Negative ion-gas reaction studies using ion guides and accelerator mass spectrometry I: SrF3-, YF3-, ZrF3-, YF4- and ZrF5- in NO2 - Eliades, J. A.; Zhao, X. -L.; Litherland, A. E.; Kieser, W. E. (ELSEVIER SCIENCE BV, 2015)
Typical accelerator mass spectrometry (AMS) ion sources readily produce useable currents of a wide variety of negative ions, including exotic species, and the sensitivity and dynamic range of AMS can be used for relatively unambiguous ion identification at low count rates. Difficulty producing negative ion currents with high fluxes (ex. when electron binding energies are small) and unambiguous identification of reaction products can be obstacles to negative ion-gas reaction studies. Thus, an AMS setup can be considered to be suitable for certain ion-gas reaction studies. Presented here are preliminary studies on interactions of SrF3-, YF3-, ZrF3-, YF4- and ZrF5- with NO2 gas at <50 eV kinetic energies using a prototype radio-frequency quadrupole (RFQ) instrument installed before the accelerator on the low-energy side of an AMS system. The superhalogen anions SrF3-, YF4- and ZrF5- were found to be highly unreactive with NO2, consistent with expected electron binding energies greater than 3.6 eV. YF3- and ZrF3- were found to have large overall attenuation cross sections in NO2 of 7.6 x 10(-15) +/- 4.4% cm(2) and 1.5 x 10(-14) 21% cm(2) respectively at the ion energies created under the experimental conditions. The major reaction channels were shown to be electron transfer and oxygen capture. A cluster NO2 center dot(YF3-) was also observed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: REACTION CELLS; ICP-MS; AMS; ENERGY; ATTENUATION; COLLISION; ANIONS